Morphology evolution of Ag/Au nanocomposites via temperature-controlled galvanic exchange to enhance catalytic activity. Issue 13 (23rd January 2017) - Park, Tae-Hyeon; Lee, Hyeri; Lee, Jaewon; Jang, Du-Jeon
Abstract : Morphology-controlled Ag/Au nanocomposites have been fabricated facilely via a modified galvanic replacement reaction using Ag nanocubes as sacrificial templates. Abstract : Morphology-controlled Ag/Au nanocomposites have been fabricated facilely via a modified galvanic replacement reaction using Ag nanocubes as sacrificial templates. The structures of the Ag/Au nanocomposites produced at the galvanic reaction temperatures of 0, 25, 55, 85, and 105 °C were found to be Au-decorated Ag nanocubes, well-defined nanoboxes, truncated nanoboxes, porous nanoboxes, and broken nanoboxes, respectively. Compared to pristine Ag nanocubes or Ag/Au nanocomposites without cavities, Ag/Au nanocatalysts with hollow interiors have been found to catalyze the reduction of rhodamine B much more rapidly in the presence of KBH4 . In particular, Ag/Au nanocomposites fabricated at 85 °C show the most efficient catalytic performance as they have the largest nanocavities, which are surrounded by the most porous walls. The high enhancement of the catalytic performance is attributed to the facilitation of rapid electron relay from BH4 − to rhodamine B via the catalytic surface, consequently lowering the kinetic barrier of the catalytic reaction. Overall, the temperature of the galvanic replacement reaction has been varied to optimize the morphology and the subsequent catalytic performance of Ag/Au nanocomposites.